Laser alloy, composite coating and preparation method of composite coating based on NiMnZnAgTaPdC powder
By adding AG, TA, and PD rare elements to the laser alloy powder ratio, the problems of impurities and Os impurities products such as Ni, MN and O and O reacting are solved, and the alloy layer's high -temperature anti -oxidation and corrosion resistance is improved.
Patent Information
- Application Number
- CN202411441118.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
In the existing laser alloying powder ratio, elements such as Ni, Mn react with O in the air to produce impurity products, resulting in cracks in the alloy layer, reducing oxidation resistance and wear resistance.
Ag, TA, and PD rare elements are added on the basis of Ni, MN, Zn, C and other common elements. The laser melting composite coating is prepared by laser melting to improve the antioxidant and corrosion resistance of the alloy layer.
The alloy layer is effectively solved by the problem of poor cracks, anti -oxidation and abrasion resistance, and improves the high temperature antioxidant performance and corrosion resistance of the material.
Smart Images

Figure CN118957388B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser alloys, and in particular to a laser alloy based on NiMnZnAgTaPdC powder, a composite coating and a preparation method of the composite coating. Background Art
[0002] As a material processing method, laser technology has broad application prospects in the manufacturing industry. At present, the production process of many industrial equipment is complex and the production cost is high, and the production cycle is long. During the service process, some parts have defects such as wear and corrosion, which cause parts failure and may cause the equipment to fail to operate normally. Therefore, improving the wear resistance, oxidation resistance and corrosion resistance of these high value-added parts will greatly increase the service life of the equipment and improve the working efficiency of the equipment. During the laser alloying process, the substrate and coating undergo rapid heating and cooling, which may cause thermal stress and distortion, especially for large and complex structure parts, which may affect the accuracy and stability of the parts.
[0003] Common laser alloying powder ratios are mainly composed of elements such as Ni, Mn, Zn, and C. In the laser alloying process, alloying powders mainly composed of Ni and Mn elements easily react with O in the air to produce products such as Ni2O3, NiO, and Mn3O4 that cannot float. These substances become impurities in the alloy layer, leading to the generation of cracks and reducing the oxidation resistance and wear resistance of the material. To this end, the present invention provides a laser alloy based on NiMnZnAgTaPdC powder, a composite coating, and a preparation method of the composite coating. Summary of the invention
[0004] In view of the above problems, the present invention provides a laser alloy, a composite coating and a preparation method of the composite coating based on NiMnZnAgTaPdC powder. Rare elements Ag, Ta and Pd are added on the basis of Ni, Mn, Zn and C elements, which not only retains the high hardness performance of the original alloy layer, but also greatly improves the oxidation resistance and wear resistance of the material, and effectively solves the technical problem that Ni and Mn as the main elements react with O to produce impurity products such as Ni2O3, NiO, MnO3, Mn3O4, etc., which leads to more cracks in the alloy layer, thereby reducing the oxidation resistance and corrosion resistance of the alloy layer.
[0005] The first object of the present invention is to provide a laser alloy based on NiMnZnAgTaPdC, which is composed of the following raw materials in percentage by mass: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C, totaling 100%.
[0006] The second object of the present invention is to provide a laser alloy composite coating, which is made of the above-mentioned laser alloy and adhesive by laser melting, and the mass ratio of the laser alloy to the adhesive is 1:0.02-0.08.
[0007] The third object of the present invention is to provide a method for preparing the above-mentioned laser alloy composite coating, comprising the following steps:
[0008] Weigh the following raw materials in mass percentage respectively: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C; add a binder to the weighed raw materials, mix them evenly, and obtain an alloy powder coating;
[0009] The alloy powder coating is applied to the surface of the substrate to form an alloy powder coating, and the alloy powder coating is overlap-scanned by laser in an inert gas atmosphere to melt and obtain a laser alloy composite coating.
[0010] As a preferred embodiment, the adhesive is composed of the following raw materials: 20% to 30% polyurethane resin, 25% to 40% polyether isocyanate, 10% to 20% phenol and 20% to 30% acetone, totaling 100%.
[0011] As a preferred implementation, the thickness of the alloy powder coating is 0.3 mm to 1.4 mm.
[0012] As a preferred implementation, the laser parameters are: laser power of 1500-4000W, laser scanning speed of 200mm / min-500mm / min, and spot diameter of 3mm-7mm.
[0013] As a preferred implementation, the inert gas is argon with a flow rate of 5 L / min to 20 L / min.
[0014] As a preferred embodiment, the substrate is titanium alloy, 17-4PH alloy, nickel-based alloy, Q235 or 304L stainless steel.
[0015] As a preferred embodiment, before applying the alloy powder coating to the surface of the substrate, the polished substrate is sent to an ultrasonic cleaning machine and cleaned in anhydrous alcohol and acetone using 20kHz to 40kHz ultrasound for 8min to 10min.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] In order to solve the technical problem in the prior art that Ni, Mn and other main elements react with O to produce impurity products such as Ni2O3, NiO, Mn3O4, etc., resulting in more cracks in the alloy layer, thereby reducing the oxidation resistance and corrosion resistance of the alloy layer. The present invention proposes to add rare elements such as Ag, Ta and Pd on the basis of common laser alloying powder ratio elements such as Ni, Mn, C and Zn, so as to solve the problems that the laser alloy coating produced by the common powder ratio is prone to deformation and cracking, poor oxidation resistance and wear resistance, etc. The interaction between the component alloys of the present invention improves the oxidation resistance and corrosion resistance of the alloy coating, which is specifically embodied in:
[0018] Ni dissolves in Mn to form a binary solid solution [Ni, Mn], which strengthens the material through local lattice strain and improves corrosion resistance; Zn and Ni form a zinc-nickel alloy, which can improve the corrosion resistance of the alloy by regulating grain boundaries, grain size and crystal orientation through heat treatment and alloying processes; Ni, Pd and Ta can form a ternary solid solution [Ta, Ni, Pd], which has a solid solution strengthening effect on the matrix and improves the corrosion resistance and thermodynamic stability of the material; Pd and Ag can form a solid solution alloy to improve the hardness and strength of the alloy; Ta and Mn elements are respectively dissolved in C element Under high temperature conditions, the elements form two hard carbides, TaC and MnC, which can effectively improve the wear resistance of the composite coating; because Ag, Ni, and Pd elements themselves are stable and not easily corroded, they have a good effect on the corrosion resistance of the composite coating surface; Ta, Pd, and Ag will react with the O element in the air to form Ta2O5, PdO, and AgO oxide films through oxidation reactions, and Zn and O will form a thin and dense basic zinc carbonate film, which quickly forms a dense oxidation protection layer to prevent further oxidation, improve the high-temperature oxidation resistance of the alloy, and also relieve stress concentration. Through the reaction between the above alloy elements, the prepared composite coating can have good oxidation resistance, corrosion resistance, and high temperature resistance.
[0019] The composite coating prepared by using Ni, Mn, Zn, Ag, Ta, Pd and C powders as raw materials provided by the present invention has 0 cracks, and the anti-oxidation rate can reach 0.37g / mm under high temperature conditions. 2 •h, wear loss can be as low as 0.76g, corrosion current as low as 2.5μA / cm 2 ; It is confirmed that the alloy powder designed by the present invention is very suitable for laser additive manufacturing.
[0020] The alloy composition of the present invention is reasonably designed, the components have strong synergy, the processing cost is reduced, and the processing efficiency is improved, so that large-scale rapid processing in factories can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1It is a schematic structural diagram of the laser alloying processing equipment used in the present invention;
[0022] Description of reference numerals:
[0023] 1. Argon gas cylinder, 2. Workbench, 3. Substrate, 4. Alloy powder coating layer, 5. Fixture, 6. Ultrasonic cleaning machine, 7. Control system, 8. Fiber laser, 9. Laser head. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0025] In view of the technical problem that Ni, Mn, C and other main elements react with O to produce impurity products such as Ni2O3, NiO, MnO, etc., resulting in more cracks in the alloy layer, thereby reducing the oxidation resistance and wear resistance of the alloy layer, the present invention provides a laser alloy based on NiMnZnAgTaPdC powder, a composite coating and a preparation method of the composite coating. On the basis of common laser alloying powder ratio elements such as Ni, Mn, Zn, C, rare elements Ag, Ta and Pd are added, and the laser alloy composite coating is prepared by laser melting, thereby improving the oxidation resistance, corrosion resistance and high temperature resistance of the alloy coating.
[0026] The technical solution of the present invention is described in detail below.
[0027] The present invention first provides a laser alloy based on NiMnZnAgTaPdC, which is composed of the following raw materials in percentage by mass: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C, which totals 100%. During the laser melting process, Ni dissolves in the Mn element to form a binary solid solution [Ni, Mn], which improves the corrosion resistance by strengthening the material through local lattice strain; Zn and Ni form a zinc-nickel alloy, which can improve the corrosion resistance of the alloy by regulating the grain boundary, grain size and crystal orientation through heat treatment and alloying processes; Ni, Pd and Ta can form a ternary solid solution [Ta, Ni, Pd], which has a solid solution strengthening effect on the matrix and can improve the strength, hardness and corrosion resistance of the alloy; Ta and Mn elements form two hard carbides TaC and MnC with C elements respectively, which can effectively improve the wear resistance of the composite coating. Because Ag, Ni and Pd elements themselves have stable and corrosion-resistant properties, they have a good effect on improving the corrosion resistance of the composite coating surface. Pd and Ag will react with O elements in the air to form PdO and AgO oxide films through oxidation reactions, and Zn and O will form a thin and dense basic zinc carbonate film, quickly forming a dense oxide protective layer. Through the reaction between alloy elements, the prepared composite coating can have good oxidation resistance, corrosion resistance and high temperature resistance.
[0028] The present invention also provides a laser alloy composite coating, which is made by laser melting the above-mentioned laser alloy and adhesive, and the mass ratio of the laser alloy to the adhesive is 1:0.02-0.08. It should be noted that the combination of laser alloy and adhesive can make the laser alloy firmly bonded to other materials, and at the same time be used for surface coating to improve the surface hardness, wear resistance or chemical stability of the material. If the mass ratio of the adhesive is too low, the laser alloy bonding effect will be poor, affecting the overall strength and durability of the composite material. Conversely, if the mass ratio of the adhesive is too high, the metal particles in the laser alloy will not be fully exposed to the surface, resulting in unsatisfactory coating effect. Taking all factors into consideration, the mass ratio of the laser alloy and the adhesive is set to 1:0.02-0.08.
[0029] The present invention also provides a method for preparing the above laser alloy composite coating, comprising the following steps:
[0030] The following raw materials are weighed in percentage by mass: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C; a binder is added to the weighed raw materials, and the mixture is mixed uniformly to obtain an alloy powder coating.
[0031] The alloy powder coating is applied to the surface of a substrate, the substrate being titanium alloy, 17-4PH alloy, nickel-based alloy, Q235 or 304L stainless steel, to form an alloy powder coating, and the alloy powder coating is overlap-scanned by laser in an inert gas atmosphere to melt and obtain a laser alloy composite coating.
[0032] As a preferred embodiment, the adhesive is composed of the following raw materials: 20% to 30% polyurethane resin, 25% to 40% polyether isocyanate, 10% to 20% phenol and 20% to 30% acetone, totaling 100%. It should be noted that polyurethane resin has excellent corrosion resistance. If the content is too low, the strength and durability of the coating will decrease. If the concentration is too high, the brittleness of the coating will increase. Polyether isocyanate can improve the wear resistance of the coating. If the content is too low, it will affect the wear resistance of the coating. If the content is too high, the brittleness of the coating will increase. Phenol has the function of adjusting rheology and increasing viscosity. Acetone can improve the fluidity of the coating so that it can be evenly coated on the surface of the substrate. Taking all factors into consideration, 20% to 30% polyurethane resin, 25% to 40% polyether isocyanate, 10% to 20% phenol and 20% to 30% acetone are selected.
[0033] The thickness of the alloy powder coating is 0.3 mm to 1.4 mm. It should be noted that if the coating thickness is too small, it cannot effectively protect the substrate from corrosion and causes uneven distribution of the coating on the surface, which is prone to wear and damage during use. If the coating thickness is too large, it will first lead to material waste. Secondly, too thick a coating may be difficult to maintain uniformity during the coating process. Finally, too thick a coating will also lead to internal stress concentration. After comprehensive consideration, the coating thickness is selected to be 0.3 mm to 1.4 mm.
[0034] The laser parameters are: laser power of 1500W to 4000W, laser scanning speed of 200mm / min to 500mm / min, and spot diameter of 3mm to 7mm. It should be noted that too low laser power will slow down the material processing speed because the material cannot be effectively melted or evaporated due to insufficient energy. Too high laser power may cause the material to burn, oxidize or deform. Too low scanning speed will reduce efficiency, and low speed will also cause uneven melting of the material. Too fast scanning speed will prevent the material from being effectively melted. A small spot diameter can achieve higher processing accuracy and details. Conversely, a large spot diameter will reduce processing accuracy, but can speed up processing speed. Combined with the above reasons, the laser power is selected to be 1500W to 4000W, the laser scanning speed is 200mm / min to 500mm / min, and the spot diameter is 3mm to 7mm.
[0035] The inert gas is argon, and the argon flow rate is 5L / min to 20L / min. It should be noted that if the flow rate is too small, the processing area will not be effectively covered by the inert gas, especially for high-temperature processing. If the flow rate is too high, the gas consumption will increase for long-term processing tasks. The type of inert gas selected based on the material properties is argon. After comprehensive consideration, the argon flow rate is selected to be 5L / min to 20L / min.
[0036] Before applying the alloy powder coating to the surface of the substrate, the surface of the substrate is cleaned. First, the polished substrate is sent to an ultrasonic cleaning machine and cleaned in anhydrous alcohol and acetone using 20kHz to 40kHz ultrasonic waves for 8min to 10min.
[0037] The present invention is specifically described below by means of the following examples and comparative examples.
[0038] Example 1
[0039] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 20% Ni, 20% Mn, 6% Zn, 19% Ag, 20% Ta, 10% Pd and 5% C.
[0040] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0041] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0042] S2. Weigh alloy powders with mass percentages of 20% Ni, 20% Mn, 6% Zn, 19% Ag, 20% Ta, 10% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0043] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 20kHz ultrasonic waves for 10 minutes.
[0044] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0045] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10 L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000 W, the laser scanning speed to 400 mm / min, and the spot diameter to 3 mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0046] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0047] Example 2
[0048] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in percentage by mass: 20% Ni, 23% Mn, 5% Zn, 16% Ag, 16% Ta, 15% Pd and 5% C.
[0049] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0050] S1, 25% by mass of polyurethane resin, 30% by mass of isocyanate, 15% by mass of phenol and 30% by mass of acetone are mixed evenly to obtain an adhesive.
[0051] S2. Weigh alloy powders with mass percentages of 20% Ni, 23% Mn, 5% Zn, 16% Ag, 16% Ta, 15% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.04 to obtain alloy powder coating.
[0052] S3, the 17-4PH substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0053] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0054] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 0.8 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 5 L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 2000 W, the laser scanning speed to 300 mm / min, and the spot diameter to 4 mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0055] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0056] Example 3
[0057] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 25% Ni, 20% Mn, 4% Zn, 15% Ag, 14% Ta, 12% Pd and 10% C.
[0058] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0059] S1, 30% by mass of polyurethane resin, 25% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0060] S2. Weigh alloy powders with mass percentages of 25% Ni, 20% Mn, 4% Zn, 15% Ag, 14% Ta, 12% Pd and 10% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.05 to obtain alloy powder coating.
[0061] S3, the nickel-based alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0062] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0063] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 0.6 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 15 L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3500W, the laser scanning speed to 250 mm / min, and the spot diameter to 5mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0064] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0065] Example 4
[0066] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 25% Ni, 25% Mn, 3% Zn, 12% Ag, 16% Ta, 14% Pd and 5% C.
[0067] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0068] S1, 20% by mass of polyurethane resin, 40% by mass of isocyanate, 15% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0069] S2. Weigh alloy powders with mass percentages of 25% Ni, 25% Mn, 3% Zn, 12% Ag, 16% Ta, 14% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.06 to obtain alloy powder coating.
[0070] S3, the Q235 substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0071] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0072] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.4 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 20L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 2500W, the laser scanning speed to 350 mm / min, and the spot diameter to 6mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0073] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0074] Example 5
[0075] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 30% Ni, 20% Mn, 2% Zn, 10% Ag, 15% Ta, 14% Pd and 9% C.
[0076] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0077] S1, 25% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 20% by mass of acetone are mixed evenly to obtain an adhesive.
[0078] S2. Weigh alloy powders with mass percentages of 30% Ni, 20% Mn, 2% Zn, 10% Ag, 15% Ta, 14% Pd and 9% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.08 to obtain alloy powder coating.
[0079] S3, the 40r substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0080] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0081] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 0.3 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 15L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 4000W, the laser scanning speed to 450 mm / min, and the spot diameter to 7mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0082] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0083] Example 6
[0084] A laser alloy based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 30% Ni, 22% Mn, 1% Zn, 13% Ag, 14% Ta, 10% Pd and 10% C.
[0085] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0086] S1, 30% by mass of polyurethane resin, 30% by mass of isocyanate, 10% by mass of phenol, and 30% by mass of acetone are mixed evenly to obtain an adhesive.
[0087] S2. Weigh alloy powders with the following mass percentages: 30% Ni, 22% Mn, 1% Zn, 13% Ag, 14% Ta, 10% Pd and 10% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.05 to obtain alloy powder coating.
[0088] S3, the 304L stainless steel substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and is cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0089] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0090] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.2 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 20L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3500W, the laser scanning speed to 500 mm / min, and the spot diameter to 5mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0091] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0092] In order to further illustrate the effect of the present invention, the present invention also sets a comparative example, as follows:
[0093] Comparative Example 1
[0094] Compared with Example 1, the difference is that the Pd element is removed, and the laser alloy is composed of the following raw materials in the following mass percentages: 30% Ni, 20% Mn, 3% Zn, 18% Ag, 19% Ta and 10% C.
[0095] A laser alloy based on NiMnZnAgTaC powder is composed of the following raw materials in mass percentage: 30% Ni, 20% Mn, 3% Zn, 18% Ag, 19% Ta and 10% C.
[0096] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0097] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0098] S2. Weigh alloy powders with mass percentages of 30% Ni, 20% Mn, 3% Zn, 18% Ag, 19% Ta and 10% C, and mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0099] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0100] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0101] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0102] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0103] Comparative Example 2
[0104] Compared with Example 1, the difference is that the Zn element is removed, and the laser alloy is composed of the following raw materials in the following mass percentages: 23% Ni, 23% Mn, 19% Ag, 20% Ta, 10% Pd and 5% C.
[0105] A laser alloy based on NiMnAgTaPdC powder, the laser alloy is composed of the following raw materials in percentage by mass: 23% Ni, 23% Mn, 19% Ag, 20% Ta, 10% Pd and 5% C.
[0106] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0107] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0108] S2. Weigh alloy powders with mass percentages of 23% Ni, 23% Mn, 19% Ag, 20% Ta, 10% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0109] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0110] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0111] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0112] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0113] Comparative Example 3
[0114] Compared with Example 1, the difference is that the Ta element is removed, and the laser alloy is composed of the following raw materials in the following mass percentages: 27% Ni, 28% Mn, 6% Zn, 19% Ag, 15% Pd and 5% C.
[0115] A laser alloy based on NiMnZnAgPdC powder, wherein the laser alloy is composed of the following raw materials in percentage by mass: 27% Ni, 28% Mn, 6% Zn, 19% Ag, 15% Pd and 5% C.
[0116] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0117] S1: 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are uniformly mixed to obtain an adhesive.
[0118] S2. Weigh alloy powders with mass percentages of 27% Ni, 28% Mn, 6% Zn, 19% Ag, 15% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0119] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0120] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0121] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0122] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0123] Comparative Example 4
[0124] Compared with Example 1, the difference is that the amount of Ni element is increased, and the laser alloy is composed of the following raw materials in the following mass percentages: 35% Ni, 20% Mn, 1% Zn, 10% Ag, 19% Ta, 10% Pd and 5% C.
[0125] A laser alloyed layer based on NiMnZnAgTaPdC powder, wherein the laser alloy is composed of the following raw materials in mass percentage: 35% Ni, 20% Mn, 1% Zn, 10% Ag, 19% Ta, 10% Pd and 5% C.
[0126] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0127] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0128] S2. Weigh alloy powders with mass percentages of 35% Ni, 20% Mn, 1% Zn, 10% Ag, 19% Ta, 10% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0129] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0130] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0131] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0132] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0133] Comparative Example 5
[0134] Compared with Example 1, the difference is that the amount of Ag element is increased, and the laser alloy is composed of the following raw materials in the following mass percentages: 20% Ni, 20% Mn, 1% Zn, 30% Ag, 14% Ta, 10% Pd and 5% C.
[0135] A laser alloy coating based on NiMnZnAgTaPdC powder is composed of the following raw materials in percentage by mass: 20% Ni, 20% Mn, 1% Zn, 30% Ag, 14% Ta, 10% Pd and 5% C.
[0136] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0137] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0138] S2. Weigh alloy powders with mass percentages of 20% Ni, 20% Mn, 1% Zn, 30% Ag, 14% Ta, 10% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0139] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0140] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0141] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0142] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0143] Comparative Example 6
[0144] Compared with Example 1, the difference is that the amount of Pd element is increased, and the laser alloy is composed of the following raw materials in the following mass percentages: 20% Ni, 20% Mn, 1% Zn, 10% Ag, 14% Ta, 30% Pd and 5% C.
[0145] A laser alloy coating based on NiMnZnAgTaPdC powder is composed of the following raw materials in percentage by mass: 20% Ni, 20% Mn, 1% Zn, 10% Ag, 14% Ta, 30% Pd and 5% C.
[0146] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0147] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0148] S2. Weigh alloy powders with mass percentages of 20% Ni, 20% Mn, 1% Zn, 10% Ag, 14% Ta, 30% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0149] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0150] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0151] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0152] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0153] Comparative Example 7
[0154] Compared with Example 1, the difference is that the amount of Mn element is increased and the amount of Ni element is reduced. The laser alloy is composed of the following raw materials in the following mass percentages: 10% Ni, 35% Mn, 5% Zn, 15% Ag, 17% Ta, 13% Pd and 5% C.
[0155] A laser alloy coating based on NiMnZnAgTaPdC powder is composed of the following raw materials in mass percentage: 10% Ni, 35% Mn, 5% Zn, 15% Ag, 17% Ta, 13% Pd and 5% C.
[0156] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0157] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0158] S2. Weigh alloy powders with mass percentages of 10% Ni, 35% Mn, 5% Zn, 15% Ag, 17% Ta, 13% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0159] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0160] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0161] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0162] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0163] Comparative Example 8
[0164] Compared with Example 1, the difference is that the amount of Zn element is increased and the amount of Ag element is reduced. The laser alloy is composed of the following raw materials in the following mass percentages: 20% Ni, 20% Mn, 20% Zn, 5% Ag, 20% Ta, 10% Pd and 5% C.
[0165] A laser alloy coating based on NiMnZnAgTaPdC powder is composed of the following raw materials in percentage by mass: 20% Ni, 20% Mn, 20% Zn, 5% Ag, 20% Ta, 10% Pd and 5% C.
[0166] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0167] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0168] S2. Weigh alloy powders with mass percentages of 20% Ni, 20% Mn, 20% Zn, 5% Ag, 20% Ta, 10% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0169] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0170] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0171] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0172] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0173] Comparative Example 9
[0174] Compared with Example 1, the difference is that the amount of Ta element is increased and the amount of Pd element is reduced. The laser alloy is composed of the following raw materials in the following mass percentages: 20% Ni, 20% Mn, 1% Zn, 19% Ag, 30% Ta, 5% Pd and 5% C.
[0175] A laser alloy coating based on NiMnZnAgTaPdC powder is composed of the following raw materials in percentage by mass: 20% Ni, 20% Mn, 1% Zn, 19% Ag, 30% Ta, 5% Pd and 5% C.
[0176] The method for preparing the laser alloy composite coating made of the above laser alloy by laser melting comprises the following steps:
[0177] S1, 20% by mass of polyurethane resin, 35% by mass of isocyanate, 20% by mass of phenol, and 25% by mass of acetone are mixed evenly to obtain an adhesive.
[0178] S2. Weigh alloy powders with mass percentages of 20% Ni, 20% Mn, 1% Zn, 19% Ag, 30% Ta, 5% Pd and 5% C, mix them evenly according to the mass ratio of laser alloy and binder of 1:0.03 to obtain alloy powder coating.
[0179] S3, the titanium alloy substrate after the surface polishing treatment is sent to the ultrasonic cleaning machine 6, and cleaned in anhydrous alcohol and 98% purity acetone using 25kHz ultrasonic waves for 10 minutes.
[0180] S4, after cleaning the surface of the substrate, use 60 mesh brown corundum sand to perform surface sandblasting roughening treatment to improve the bonding strength between the coating and the substrate.
[0181] S5, evenly apply the alloy powder coating on the surface of the cleaned substrate to form an alloy powder coating layer 4 with a thickness of 1.0 mm, dry it, place the substrate 3 coated with the alloy powder coating on the workbench 2, clamp it with the fixture 5, and use a spray gun to preheat the substrate and the coating to reduce the internal stress during the laser alloying operation. Then, use the fiber laser 8 to perform laser alloying operation on the treated area to finally form an alloy coating; specifically: open the argon bottle 1 to deliver the argon gas flow at a flow rate of 10L / min to the laser head 9 and blow it to the surface of the substrate 3; turn on the fiber laser 8, adjust the laser power to 3000W, the laser scanning speed to 400 mm / min, and the spot diameter to 3mm, and irradiate the laser beam through the laser head 9 to the surface of the alloy powder coating layer 4, and control the workbench 2 to move left and right along the X-axis, and the laser head 9 to move forward and backward along the Y-axis or up and down along the Z-axis through the control system 7, so that the laser beam performs laser alloying treatment on the alloy powder coating layer 4.
[0182] S6, after the laser beam scans the alloy powder coating layer 4, the optical fiber laser 8 is turned off, the argon gas bottle 1 is turned off, and the control system 7 controls the workbench 2 to drive the laser head 9 to return to the original position.
[0183] The properties of the laser alloy composite coatings based on NiMnZnAgTaPdC powder provided in the above Examples 1 to 6 and Comparative Examples 1 to 9 were tested respectively, and the results are shown in Table 1.
[0184] Table 1 Performance test table of laser alloy composite coatings of the embodiments of the present invention and comparative examples
[0185]
[0186] As shown in Table 1, the laser alloyed surface based on NiMnZnAgTaPdC powder prepared by the present invention has excellent wear resistance, corrosion resistance and high temperature oxidation resistance. The alloyed layers of Examples 1 to 6 of the present invention did not produce cracks, and the corrosion current was as low as 2.5 μA / cm 2 Under high temperature conditions, the wear loss is as low as 0.76g and the oxidation rate is 0.37g / mm 2 •h, while in Comparative Examples 1 to 9, after adjusting the components and mass percentages of the laser alloying powders, respectively, Comparative Examples 1 to 3 lack a certain rare element, and Comparative Examples 4 to 9 increase or decrease the proportion of a certain element, the performance of the obtained laser alloying layers is not ideal, which is specifically manifested in a large number of cracks on the surface of the laser alloying layer, reduced corrosion resistance, and increased oxidation area.
[0187] The laser alloy composite coatings obtained in the above comparative examples 1 to 9 have poor performance, and the main reasons are:
[0188] In Comparative Example 1, since the Pd element itself has corrosion resistance in a high temperature environment, the lack of the Pd element will cause the corrosion resistance of the alloy in a high temperature environment to decrease. The lack of the Pd element also increases the proportion of other elements, resulting in the destruction of the reaction between the elements, which is not conducive to the improvement of the alloy performance.
[0189] In Comparative Example 2, due to the active chemical properties of Zn, a thin and dense basic zinc carbonate film is formed on the surface in the air at room temperature, which can prevent further oxidation and improve the oxidation resistance of the alloy. Therefore, the lack of Zn will lead to a decrease in the oxidation resistance and corrosion resistance of the coating alloy.
[0190] In comparative example 3, Ta has extremely high corrosion resistance and will not react with hydrochloric acid, concentrated nitric acid and aqua regia even at high temperature. However, Ta will generate tantalum carbide at 2800°C, which is mainly used in cemented carbide because tantalum has extremely strong corrosion resistance. TaC can improve the hardness, strength and melting point of the alloy. When it is missing, the corrosion resistance and wear resistance will be reduced, which is not conducive to the improvement of performance.
[0191] In Comparative Example 4, since the chemical properties of Ni element itself are relatively active, it reacts with halogen when heated to produce a large amount of impurities. The increase in the proportion of Ni element reduces other elements, resulting in a decrease in the performance of the alloy layer.
[0192] In comparative example 5, the increase in the proportion of Ag will increase the proportion of other elements, resulting in the destruction of the reaction between elements, which is not conducive to the improvement of alloy performance and will eventually reduce the oxidation resistance and corrosion resistance of the alloy layer.
[0193] In comparative example 6, increasing the proportion of Pd element will reduce the proportion of other elements. Pd can absorb a large amount of hydrogen, causing the volume to expand significantly, becoming brittle or even breaking into pieces, increasing the brittleness of the alloy, reducing the Ag content, and reducing the amount of solid solution formed by Pd and Ag. At the same time, the balance of the reaction process between elements is destroyed, further reducing the performance, and ultimately leading to more cracks in the alloy layer and reduced performance.
[0194] In Comparative Example 7, the Mn element is increased and the Ni element is reduced: since Ni can form solid solutions with Pd, Ta, and Mn elements, reducing the Ni element will reduce the generated solid solutions and increase the proportion of the Mn element. During the heating process, the Mn element will react with the O element in the air to generate MnO2 at 450°C, Mn2O2 below 800°C, and Mn3O4 above 800°C, generating a variety of impurities, which is not conducive to performance improvement.
[0195] In Comparative Example 8, the Zn element is increased and the Ag element is decreased: the Ag element has relatively stable properties, good thermal conductivity, and more uniform energy transfer. Ag will react with the O element in the air through oxidation to form a dense AgO oxidation protective layer, which prevents further oxidation and will cause the reaction process between the elements to be destroyed.
[0196] In Comparative Example 9, the Ta element is increased and the Pd element is reduced: Ni, Pd and Ta can form a ternary solid solution of [Ta, Ni, Pd]. When the Ta ratio increases and the Pd ratio decreases, the solid solution content will decrease. At the same time, Pd will react with the O element in the air to form a PdO oxide film through an oxidation reaction, which is not conducive to improving the wear resistance.
[0197] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A laser alloy composite coating based on NiMnZnAgTaPdC, characterized in that: The laser alloy composite coating is composed of the following raw materials in percentage by mass: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C, totaling 100%; The preparation method of the laser alloy composite coating made of the above laser alloy and adhesive by laser melting comprises the following steps: The following raw materials are weighed in mass percentage respectively: 20% to 30% Ni, 20% to 25% Mn, 1% to 6% Zn, 10% to 20% Ag, 14% to 20% Ta, 10% to 25% Pd and 5% to 10% C, which total 100%; an adhesive is added to the weighed raw materials, and mixed evenly to obtain an alloy powder coating; the mass ratio of the laser alloy to the adhesive is 1:0.02 to 0.08; the adhesive is composed of the following raw materials in mass fraction: 20% to 30% polyurethane resin, 25% to 40% polyether isocyanate, 10% to 20% phenol and 20% to 30% acetone, which total 100%; The alloy powder coating is applied to the surface of the substrate to form an alloy powder coating, and the alloy powder coating is overlap-scanned by laser in an inert gas atmosphere to melt and obtain a laser alloy composite coating.
2. The laser alloy composite coating based on NiMnZnAgTaPdC according to claim 1, characterized in that: The thickness of the alloy powder coating is 0.3 mm to 1.4 mm.
3. The laser alloy composite coating based on NiMnZnAgTaPdC according to claim 1, characterized in that: The laser parameters are: laser power of 1500W to 4000W, laser scanning speed of 200mm / min to 500mm / min, and spot diameter of 3mm to 7mm.
4. The laser alloy composite coating based on NiMnZnAgTaPdC according to claim 1, characterized in that: The inert gas is argon, and the flow rate of the argon is 5 L / min to 20 L / min.
5. The NiMnZnAgTaPdC-based laser alloy composite coating according to claim 1, characterized in that: The substrate is titanium alloy, 17-4PH alloy, nickel-based alloy, Q235 or 304L stainless steel.
6. The NiMnZnAgTaPdC-based laser alloy composite coating according to claim 1, characterized in that: Before the alloy powder coating is applied to the surface of the substrate, the polished substrate is sent to an ultrasonic cleaning machine and cleaned in anhydrous alcohol and acetone in turn using 20kHz to 40kHz ultrasonic waves for 8min to 10min.
Citation Information
Patent Citations
High-entropy alloy double technology preparation method
CN111349800A
Laser alloy based on NiCuMoNbReYbC powder, composite coating and preparation method of composite coating
CN117684067A